KORELASI ANTARA KELIMPAHAN VEGETASI MANGROVE DAN KERANG TOTOK Polymesoda erosa DENGAN FAKTOR LINGKUNGAN DI SEGARA ANAKAN, CILACAP - Mia Azizah (JURNAL SAINS NATURAL, 2014)
Correlation Between Abundance of Mangrove Vegetation and Totok Clam (Polymesoda erosa) to Environmental Factors in Segara Anakan, Cilacap           Segara Anakan ecosystem is one of the largest estuary in Java which has a high biodiversity. One of the biota totok clam (Polymesoda erosa ) that live in  mangrove forests. These clams have high economic value. The study aimed to determine the correlation of abundance between mangrove community and totok clam (P. erosa) , because of  abiotic environmental factors  in Segara Anakan , Cilacap. Research using survey methods and sampling techniques. Sampling point were 11 stations and were 3 plot sampling respectively. The data  analyzed using correlation analysis of BIO - ENV. The correlation value of the environmental factors and mangrove community was 0.362 , and the correlation value of the environmental factor and the abundance of P. erosa was 0.412. The correlation value of mangrove vegetation with an abundance Polymesoda erosa had  a value of 0.468. Keywords: correlation, mangroves, Polymesoda erosa, Segara AnakanABSTRAK        Ekosistem Segara  Anakan merupakan salah satu estuaria terbesar di Pulau Jawa yang memiliki keanekaragaman hayati yang tinggi. Salah satu biota yang ada adalah kerang totok(Polymesoda erosa) yang hidup berasosiasi dalam hutan mangrove. Kerang ini memiliki nilai ekonomis  yang cukup tinggi. Penelitian ini bertujuan untuk mengetahui korelasi antara kelimpahan komunitas mangrove dan kelimpahan kerang totok (P. erosa), yang disebabkan faktor lingkungan abiotik P. erosa di Segara anakan, Cilacap. Penelitian menggunakan metode survei dan teknik pengambilan sampel. Titik sampling dibuat 11 stasiun dengan tiap stasiun diambil 3 plot. Data dianalisis dengan menggunakan analisis korelasi BIO-ENV. Nilai korelasi faktor lingkungan dengan struktur komunitas mangrove sebesar 0,362, dan nilai korelasi faktor lingkungan dengan kelimpahan P. erosa sebesar 0,412. Nilai korelasi vegetasi mangrove dan kelimpahan kerang totok memiliki  nilai sebesar 0,468.Kata kunci: korelasi, mangrove, Polymesoda erosa, Segara AnakanSegara Anakan ecosystem is one of the largest estuary in Java which has a high biodiversity. One of the biota totok clam(Polymesoda erosa ) that live in  mangrove forests.These clams have high economic value. The study aimed to determine the correlation of abundance between mangrove community and totok clam (P. erosa) , because of  abiotic environmental factors  in Segara Anakan , Cilacap. Research using survey methods and sampling techniques. Sampling point were11 stations and were 3 plot sampling respectively. The data  analyzed using correlation analysis of BIO - ENV. The correlation value of the environmental factors and mangrove community was 0.362 , and the correlation value of the environmental factor and the abundance of P. erosa was 0.412.The correlation value of mangrove vegetation with an abundance Polymesoda erosa had  a value of 0.468. Keywords: correlation, mangroves, Polymesoda erosa, Segara Anakan